Roles of the sequence encoding tobacco etch virus capsid protein in genome amplification: requirements for the translation process and a cis-active element. - Mahajan, S (1996)
The roles of the capsid protein (CP) and the CP coding sequence of tobacco etch potyvirus (TEV) in genome amplification were analyzed. A series of frameshift-stop codon mutations that interrupted translation of the CP coding sequence at various positions were introduced into the TEV genome. A series of 3' deletion mutants that lacked the CP coding sequence beyond each of the frameshift-stop codon mutations were also produced. In addition, a series of 5' CP deletion mutants were generated. Amplification of genomes containing either frameshift-stop codon insertions after codons 1, 59, 103, and 138 or genomes containing the corresponding 3' deletions of the CP coding sequence was reduced by 100- to 1,000-fold relative to that of the parental genome in inoculated protoplasts. In contrast, a mutant containing a frameshift-stop codon after CP position 189 was amplified to 27% of the level of the parental virus, but the corresponding 3' deletion mutant lacking codons 190 to 261 was nonviable. Deletion mutants lacking CP codons 2 to 100, 2 to 150, 2 to 189, and 2 to 210 were amplified relatively efficiently in protoplasts, but a deletion mutant lacking codons 2 to 230 was nonviable. None of the amplification-defective frameshift-stop codon or deletion mutants was rescued in transgenic cells expressing TEV CP, although the transgenic CP was able to rescue intercellular movement defects of replication-competent CP mutants. Coupled with previous results, these data led to the conclusions that (i) TEV genome amplification requires translation to a position between CP codons 138 and 189 but does not require the CP product and (ii) the TEV CP coding sequence contains a cis-active RNA element between codons 211 and 246. The implications of these findings on mechanisms of RNA replication and genome evolution are discussed.